Niche-induced cell death and epithelial phagocytosis regulate hair follicle stem cell pool - Mesa, Kailin R.; Rompolas, Panteleimon; Zito, Giovanni; Myung, Peggy; Sun, Thomas Y.; Brown, Samara; Gonzalez, David G.; Blagoev, Krastan B.; Haberman, Ann M.; Greco, Valentina (Nature (London), 2015)
Mouse hair follicles in the skin cycle between growth and regression, while maintaining a pool of stem cells for continued regeneration; here, live imaging is used to show that a combination of niche-induced stem cell apoptosis and epithelial phagocytosis underlies regression, regulating the stem cell pool. Mechanisms of tissue regression Mouse hair follicles in the skin cycle between growth and regression, while maintaining a pool of stem cells for regeneration. Valentina Greco and colleagues used imaging in live mice to show that regression involves a combination of niche-induced stem cell apoptosis and epithelial phagocytosis. Dead cells are removed from the follicle by their neighbouring epithelial cells through phagocytosis. The authors also show that regression is essential for the reduction of the overall stem cell pool as part of tissue homeostasis. Tissue homeostasis is achieved through a balance of cell production (growth) and elimination (regression) 1 , 2 . In contrast to tissue growth, the cells and molecular signals required for tissue regression remain unknown. To investigate physiological tissue regression, we use the mouse hair follicle, which cycles stereotypically between phases of growth and regression while maintaining a pool of stem cells to perpetuate tissue regeneration 3 . Here we show by intravital microscopy in live mice 4 , 5 , 6 that the regression phase eliminates the majority of the epithelial cells by two distinct mechanisms: terminal differentiation of suprabasal cells and a spatial gradient of apoptosis of basal cells. Furthermore, we demonstrate that basal epithelial cells collectively act as phagocytes to clear dying epithelial neighbours. Through cellular and genetic ablation we show that epithelial cell death is extrinsically induced through transforming growth factor (TGF)-β activation and mesenchymal crosstalk. Strikingly, our data show that regression acts to reduce the stem cell pool, as inhibition of regression results in excess basal epithelial cells with regenerative abilities. This study identifies the cellular behaviours and molecular mechanisms of regression that counterbalance growth to maintain tissue homeostasis.